AKRB STRATEGI HUMAS KABUPATEN PANDEGLANG DALAM MENJAGA CITRA PEMERINTAH - Prayoga Dwiki Subastyan; Annisarizki; Dwi Nurina Pitasari* (Jurnal Ilmu Komunikasi AKRAB, 2023)
ABSTRACTPublic Relations of the Pandeglang Regency Government is a bridge for thepublic to find out information about policies or programs implemented byPandeglang Regency Government. Public Relations of Pandeglang RegencyGovernment also has an important role in shaping, improving or maintaining imageof Pandeglang Regency Government. This study aims to determine the strategy forcompiling and conveying the messages as well as information disseminationstrategies implemented by the Public Relations of Pandeglang Regency through themedia. This research uses Post-positivism paradigm. The method used is a casestudy with a qualitative approach. Data collection techniques used in this study wereobservation, interviews and documentation. The informant selection technique usedpurposive sampling. The theory used in this research is the theory of informationintegration. The results showed that the strategy used by Public Relations ofPandeglang Regency was to maintain image of the government in the process ofcompiling and conveying the messages in a structured, informative manner andchemistry at work. The Public Relations strategy of Pandeglang Regency indisseminating information through the media is to establish good relations with the media crew and use social media, especially the Instagram social media accountwhich is managed by the Public Relations and Protocol of Pandeglang Regency.Keywords: Public relations strategy, Pandeglang Regency, government image